The 'Untranslatability' of Culture: Ahmadou Kourouma's Allah n'est pas obligé. (17th June 2016) - Corcoran, Patrick
Abstract: This article begins with an interrogation of the very concept of 'cultural translation' and argues that it involves a loosely applied metaphorical use of the term 'translation' which has been authorized by the way various related disciplines (ethnograpy, anthropology, postcolonial literary and cultural studies, and translation studies) have pursued common preoccupations in recent years. Within this general context of scepticism about the translatabilty of cultures, the article goes on to propose a detailed analysis of Ahmadou Kourouma's novel Allah n'est pas obligé . The novel is a multilingual text in the sense that the trope of 'translation' is omnipresent as the child-soldier protagonist constantly resorts to dictionaries to facilitate his role as narrator. I argue that the obsession with translation, along with a number of other rhetorical devices that Kourouma draws upon, serves ultimately to demonstrate the 'untranslabilty' of the child-soldier's experience.